Students' knowledge, perceptions and practice towards direct-to-consumer advertising of pharmaceuticals in Malaysia / Kamaliah Md Saman ... [et al.] - Md Saman, Kamaliah; Mahusin, Mohd Khairul Anuar; Loganathan Fahrni, Mathumalar; Ismail, Hasnah (Faculty of Pharmacy, 2021)
Direct-to-consumer advertising (DTCA) of pharmaceuticals is increasingly popular and has both benefits and harm. We examined the knowledge, perception and practice (KAP) of Malaysian students. In this cross-sectional study, 200 questionnaires were returned. 31% of students had good; 59.5% had fair, and 9.5% had poor knowledge, on the types of drugs and information permitted for DTCA. Health-related programme students scored higher. Internet was the most influential media. Age, gender, the programme students were enrolled in, year of study, and having a family member who was a healthcare worker were significant predictors of KAP (p<0.05). A significant, positive association between knowledge on drugs that can be advertised and the practice of requesting for these drugs at the general practitioners' clinics were observed (p=0.045). Many preferred advertised drugs over non-advertised, and although the former costed more, they indicated that the quality of advertised drugs is no better than those prescribed by the doctors. Respondents believed that advertisements were educational although these advertisements provided insufficient information on adverse effects. Ease of use and medication costs were the main information looked for in advertisements. Two-thirds of the sampled students believed that these advertisements do not harm the doctor-patient relationship; 62% would have first consulted a doctor and if he or she refused to prescribe, they would not seek the prescription from another doctor. In conclusion, students represent a population of end-users of DTCA whose practices are heavily influenced by information available through DTCA. Accurate, responsible, and lawful advertising should be enforced by the authorities